Efficacy and safety of immune checkpoint inhibitors in patients with advanced intrahepatic cholangiocarcinoma - Peng, Ziting; Dong, Jianhui; Tang, Shuyao; Shi, Jiaxu; Shi, Tongdong (Frontiers in Oncology, 2025)
BackgroundTo assess the efficacy and safety of PD-1 and PD-L1 immune checkpoint inhibitors (ICIs) in managing advanced intrahepatic cholangiocarcinoma (ICC).MethodsA retrospective analysis of treatment data for patients with advanced ICC who received ICIs at the Second Affiliated Hospital of Chongqing Medical University from the inception of the inpatient medical record database until 30 April 2024. The analysis concentrated on the safety and efficacy of the treatment. The primary endpoint was progression-free survival (PFS), while the secondary endpoints included overall survival (OS) and safety. The Kaplan-Meier method was employed to plot survival curves, and differences between groups were assessed using log-rank tests.Results96 patients diagnosed with ICC were included, comprising 60 males (62.50%) and 36 females (37.50%). 85 patients exhibited disease progression, 22 patients succumbed, and 38 patients were lost to follow-up finally. Those who initiated immunotherapy promptly following first-line antitumor treatment exhibited a notably prolonged PFS compared to those experiencing tumor progression (5.63 months (95%CI: 3.12~8.14) vs 2.50 months (95%CI: 1.83~3.17), P=0.002). However, no significant disparity in the PFS with immunotherapy in different lines therapy(P=0.406) and the OS was observed between the two groups(P=0.360). 18 patients (18.75%) experienced treatment-emergent adverse events (AEs), with 3 patients encountering AEs of grade ≥3. All patients returned to normal after symptomatic treatment.ConclusionsIn patients with advanced ICC, the timely initiation of ICIs as adjuvant therapy following first-line antitumor treatment can result in favorable efficacy and a good safety profile.